The Effect of Quenching Process on Chrome and Carbon-Coated Carbon Steel on Hardness Level and Microstructure - Monica, Zelvia (Universitas Sultan Ageng Tirtayasa, 2025)
Along with the development of mining industry technology and heavy equipment industry which are in dire need of wear resistant steel, wear resistant steel applications are demanded to be able to meet the needs of the industry. In excavator buckets, wear resistant steel is really needed due to its continuous use rubbing against the soil material, therefore the steel is carried out hardfacing. As an alternative, a Chrome coating and the addition of Carbon powder can be modified on the E-7018 electrode which is commonly used for joining metals. After going through the hardfacing process again the Quenching process is expected to further increase the hardness of the surface of the material. The material in this study was low carbon steel with 9 specimens, 1 raw material specimen, 4 specimens by cooling the Coolant and 4 specimens without treatment. Each is divided into electrodes coated with Chrome, Carbon, Chrome + Carbon. Based on the research results obtained, it is known that the addition of Carbon to low carbon steel that has been cooled by cooling shows the martensitic microstructure and produces the highest hardness of 348.98 VHN compared to the electrodes that are not treated. In specimens E-7018 without treatment showed microstructure of ferrite and produced the lowest hardness of 191.26 VHN.